Analysis of Funny Metaphor Used in Instagram’s Captions - Muhammad Fitriyanto; Ismara Vernanda; Vita Lutfiah; Yudhistira Taufiqi Mulyana; Husnul Athiya (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2020)
This paper aims to examine the metaphors used in "Awreceh.id" Instagram captions that the researchers considered as funny. Metaphors are often used in everyday life consciously or unconsciously, especially in terms of expressing things to make it funny. Metaphors are not only used in speech but also usually found in many writings in everyday life, such as using metaphors to make captions in Instagram posts. The researchers chose funny metaphors because there are different semantic reasons. Apart from that, other funny metaphors can also be interpreted linguistically for semantic and pragmatic reasons as they depict funny references and would even be funny without the metaphorical medium and a bit of pun. The researchers used a descriptive qualitative method to depict and describe the metaphors contained in the captions of Awreceh.id's Instagram content from January to March as additional elements used to make the content more entertaining. In collecting data, documentation methods and techniques of screenshots, transcripts, and notes were used. Based on the problem, this study examines the use of Lakoff and Johnson's interpretation of the metaphor in the Instagram caption of the amusing account "Awreceh.id." Following a classification of the data by Lakoff and Johnson based on the sort of conceptual metaphor used, a description of the metaphor's intended use is provided. The researchers analyzed the types of conceptual metaphors commonly used in instagram captions by community on millennial awreceh.id account followers based on Lakoff and Johnson's theory of metaphors. In explaining the research results, formal and informal methods were used. According to the analysis's findings, the Instagram captions for the account "Awreceh.id" contained structural metaphors, orientational metaphors, and ontological metaphors. It means that the use of conceptual metaphors in constructing the captions is necessary in terms of making it more entertaining.